Current trends and challenges in South African higher education - Singh, Rachael Jesika (South African Journal of Higher Education, 2016)
In the last five years, higher education teaching and learning in South Africa has experienced a significant shift as focus has turned inwards to teaching, learning and research practice of individual institutions. A specific area of interest has been on teacher education as South Africa struggles to train enough teachers to meet its high demand. A need for increased postgraduate throughput has forced higher education institutions to focus on research capacity building in the areas of supervision, publications and staff qualifications. Amidst these are the challenges of large classes, recurriculation, and development and use of local African languages. Reflecting on these issues is the focus of this introductory article.